Researching the lived experiences of cancer patients with malignant fungating wounds - Rowan, Sara; Moffatt, Christine; Olden, Anthony (Mark Allen Healthcare, 2015)
Background: Researching the experiences of terminally ill patients with disfiguring wounds is likely to be a challenge anywhere, and this investigation came face-to-face with different attitudes on the part of both patients and nurses and doctors in England (the South-East) and Italy (Tuscany). Aim: To highlight the complexity of researching sensitive subjects and the difficulties encountered from the perspective of the researcher(s). Methods: Fourteen patients were interviewed. In England access was relatively straightforward, with nurses linked to the hospice doing most of the recruitment. Access was more difficult in Italy, with some doctors expressing opposition. Discussion: How ethical is it to treat dying patients as subjects for research? How does research of this kind vary from one culture to another? Conclusions: Interviewees can find it therapeutic to talk about their experiences to a sympathetic listener ― although the listening does pose a considerable strain on the researcher.